Sectoral Interconnectedness: insight from five sectors in ‘smart’ urban planning (Energy, Transport, Waste Management, Buildings, and Cities) - Onyango, Vincent; Forghaniallahabadi, Maryam; Santos, Sandra Costa; Gazzola, Paola (European Scientific Journal, ESJ, 2025)
‘Smart’ urban planning has become integral to addressing contemporary urban challenges, with sectoral interconnectedness at the core of achieving sustainable, efficient, and resilient cities. This paper explores the level of interconnectedness across smart energy, Smart Transport, Smart Waste Management, Smart Buildings, and Smart Cities. This scope encompasses the complexities from site to city-wide scale. A mixed-method approach of qualitative thematic coding and quantitative correlation analysis, within NVivo’s suit of cluster analysis, was employed. Strong interconnectedness was found between Energy and Transport, driven by digital transformation and data-driven decision-making. Weak interconnectedness was found between transformative cross-sectoral (CS) goals, e.g., climate adaptation and sustainability, and Waste Management and Building sectors, indicating that these critical components are not yet fully integrated into smart urban frameworks. Smart Cities were the most interconnected, acting as a central platform where CS goals like sustainability, digital transformation, and real-time data utilization are most connected to. While digital tools foster intersectoral connection, sectoral silos or inconsistent interoperability may hinder the realization of holistic smart urban outcomes. The results underscore the need for cohesive frameworks that methodologically align CS goals in the sectors, ensuring that technological innovations relate to long-term environmental and social goals. This paper offers actionable insights for policymakers and urban planners to enhance cross-sector collaboration, optimize urban systems, and achieve integrated, adaptive and sustainable smart urban planning.